A Systematic Literature Review on Slow Tourism and Its Implications to the Uttarakhand State of India - BHANDARI, Jitender; RANA, Vinay; SINGH, Shalini (Journal of Environmental Management and Tourism; Vol 15 No 2 (2024): JEMT, Volume XV, Issue 2(74), Summer 2024DO - 10.14505/jemt.v15.2(74).12, 2024)
This paper explores how slow tourism might promote sustainability in India. Slow tourism is a sustainable travel strategy that prioritizes high-quality travel experiences above quantity and aims to protect the environment, promote local culture, and increase travelers' happiness. This study examines the main ideas, themes, and behaviors related to slow tourism through a thorough literature assessment. It assesses their applicability to India's socio-cultural and ecological contexts. It draws attention to the potential of slow tourism to promote sustainable development through strengthening local economies, protecting the environment, and cultivating an awareness of the natural and cultural history of the region. The report also evaluates the potential and challenges for slow tourism in India and makes recommendations for future study and policy formation. This study highlights slow tourism's potential to advance sustainability in India's tourist industry, using Uttarakhand as a relevant case study.